The politics of resilience and transatlantic order: enduring crisis? - Friedrichs, Gordon; Harnisch, Sebastian; Thies, Cameron G. (Routledge studies on challenges, crises and dissent in world politics, 2019)
Theorizing transatlantic crisis resilience : an introduction / Sebastian Harnisch, Cameron G. Thies, and Gordon Friedrichs -- America first, NATO second : deciphering the Dutch-American alliance in post-9/11 out-of-area operations / Arthur ten Cate -- Ukraine crises and the limits of transatlantic cooperation / Sergiy Kudelia -- Thaw or containment? : NATO divisions over Russia and the quest for alliance credibility / Sebastian Mayer -- New politics of burden-sharing in NATO? : crisis, conflict, and resilience in an era of populism / Serena Simoni and Sebastian Harnisch -- Preventing crisis militarization : the European Union, the United States and the Iranian nuclear program / Sebastian Harnisch -- The Joint Comprehensive Plan of Action at a crossroads / David Santoro -- Business as usual or norm promotion? : divergent modes and consequences of transatlantic crisis resilience in cybersecurity and data protection after the Snowden revelations / Wolf Schünemann -- A crisis of trust : transatlantic cybersecurity relations in the post-Snowden era / Ryan C. Maness -- A coming transatlantic clash over international development banks? : the case of the Asian infrastructure development bank / Klaus Rohland -- International development banks in the aftermath of the global financial crisis : a turn from transatlanticism? / Cameron G. Thies -- "Brexit" and the politics of resilience in the U.S.-UK special relationship / Kai Oppermann -- A new grand bargain? : Trumpian populism and shifts in liberal economic order / Gordon Friedrichs -- The logic of crisis resilience in transatlantic relations / Sebastian Harnisch, Cameron G. Thies, Gordon Friedrichs.